2017
DOI: 10.1039/c6fd00193a
|View full text |Cite
|
Sign up to set email alerts
|

Laser-flash-photolysis-spectroscopy: a nondestructive method?

Abstract: Herein, we report the effect of the laser illumination during the diffuse-reflectance laser-flash-photolysis measurements on the morphological and optical properties of TiO powders. A grey-blue coloration of the TiO nanoparticles has been observed after intense laser illumination. This is explained by the formation of nonreactive trapped electrons accompanied by the release of oxygen atoms from the TiO matrix as detected by means of UV-vis and EPR spectroscopy. Moreover, in the case of the pure anatase sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
(101 reference statements)
2
15
0
Order By: Relevance
“…intense flash xenon lamp) by measuring the transmittance for transparent samples or the reflectance for opaque samples, respectively, before and after the laser excitation. 69 However, when the efficiency of the photoexcitation process is limited by the fast decay (within a few picoseconds) of the photogenerated charges, the fact that the remaining charges have a microsecond lifetime makes no difference, and unravelling the dynamics at short time scales becomes crucial. Thus, in order to capture the entire extent of the photoexcited state decays and the fast dynamics of photocatalytic systems, subpicosecond time resolution is needed.…”
mentioning
confidence: 99%
“…intense flash xenon lamp) by measuring the transmittance for transparent samples or the reflectance for opaque samples, respectively, before and after the laser excitation. 69 However, when the efficiency of the photoexcitation process is limited by the fast decay (within a few picoseconds) of the photogenerated charges, the fact that the remaining charges have a microsecond lifetime makes no difference, and unravelling the dynamics at short time scales becomes crucial. Thus, in order to capture the entire extent of the photoexcited state decays and the fast dynamics of photocatalytic systems, subpicosecond time resolution is needed.…”
mentioning
confidence: 99%
“…It should be mentioned here that these nonreactive Ti 3+ centers are different from those Ti 3+ species which were detected here by the transient absorption in the visible range. The former are created by the surface reconstruction and remain in the lattice exhibiting absorption in the entire wavelength range as has been shown in the previous publication . Moreover, the formation of these long-lived Ti 3+ species in TiO 2 is most likely complete before the measurement of the transient absorption starts, i.e., 100 ns after the laser pulse.…”
Section: Discussionmentioning
confidence: 51%
“…In accordance with this study, the transition or rather the absorption coefficient of the trapped holes can be influenced by their interaction with the counterions. In our previous publication we have shown that irreversible changes of TiO 2 occur during pulse illumination with high laser excitation densities. A surface reorganization accompanied by the release of oxygen atoms from the lattice has been observed followed by the formation of nonreactive Ti 3+ centers in both phases that are anatase and rutile TiO 2 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Laser flash photolysis (LFP) is a broadly used technique for investigating fundamental photoprocesses, such as ET kinetics, the formation of short-lived excited states, formation of radical ions and their subsequent recombination, and transient species formed during photoionization [29][30][31]. The intense laser pulse generates a short-lived transient species of a sample that leads to changes in the absorption characteristics.…”
Section: Introductionmentioning
confidence: 99%